(untitled) (Innovative professional education, 2025)
Education reform forced teachers to develop, self-realize and improve their creative potential. The modernization of traditional and the introduction of innovative teaching methods create conditions for the qualitative formation of digital competence of students in the conditions of innovative development of the educational environment of the general secondary education institution. Today, it has already become clear that previously effective pedagogical techniques and teaching methods are not so effective for the formation of a competitive specialist.